Pengaruh Cara Pengeringan terhadap Perolehan Kadar Senyawa Fenolat dan Aktivitas Antioksidan dari Daun Jambu Biji (Psidium guajava Linn.) - Harrizul Rivai; Hasnah Hasnah; Mardius Syarif (Jurnal Farmasi Higea, 2009)
A determination of phenolic compounds and antioxidant activity from Psidium guajava leaf by UV–Visible spectrophotometry has been done. The determination of phenolic compounds was carried out according to Folin-Ciocalteau method and antioxidant activity was evaluated by DPPH method, calculated as gallic acid equivalent (GAE). The determination of phenolic compound showed that the fresh sample , air drying, oven drying 40C and oven drying 60C contained 11.207; 4.129; 4.525 and 8.357 mg GAE/g Sample, IC50 of these sample were 0.218; 0.515; 0.50 and 0.315 mg/g, respectively.